Parents' and child characteristics in relation to prental involvement in children's schooling. - Panganiban, Rosario P; Provido, Lores Leticia B. (1999.)
This study sought to find out the strength and direction of relationship between and among parental involvement and its predictors. Parents' perceived self-efficacy, parents' expectation, birth order and child academic achievement were hypothesized to influence the degree of parental involvement. Fifty-two parents were chosen from the population through purposive random sampling. Different scales were used to measure parental involvement, expectation and self-efficacy. Multiple correlation showed that there was a significant correlation between parental involvement and efficacy (r = .232; p_ < .05), parental involvement and grade ( r = .361; p_ < .05) and birth order and expectation (r = .242; p_ < .05). The test for two independent means further revealed that parents with high parental involvement have children with good academic standing compared to children with low parental involvement.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Parents; Children -- Characteristics